2011
DOI: 10.1016/j.neurobiolaging.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive training intervention improves modality-specific attention in a randomized controlled trial of healthy older adults

Abstract: Age-related deficits in cognitive and sensory function can result in increased distraction from background sensory stimuli. This randomized controlled trial investigated the effects of a cognitive training intervention aimed at helping healthy older adults suppress irrelevant auditory and visual stimuli. Sixty-six participants received 8 weeks of either the modality-specific attention training program or an educational lecture control program. Participants who completed the intervention program had larger impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
129
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 79 publications
(94 reference statements)
8
129
2
1
Order By: Relevance
“…Consistent with research reporting that transfer depends on the type and duration of training (Klingberg, 2010;Owen et al, 2010;van Muijden et al, 2012), interventions using adaptive and repetitive training sessions (Borella et al, 2010;Carretti et al, 2012;Mozolic et al, 2011;Richmond et al, 2011;Smith et al, 2009) Maintenance was reported in nine out of ten cognitive training interventions, lasting between 3 and 6 months. These findings are consistent with reports from other reviews that training effects can be preserved for at least a couple of months in both memory and executive domains (Reijnders et al, 2012;Verhaeghen, 2000).…”
Section: Transfer and Maintenancesupporting
confidence: 67%
See 3 more Smart Citations
“…Consistent with research reporting that transfer depends on the type and duration of training (Klingberg, 2010;Owen et al, 2010;van Muijden et al, 2012), interventions using adaptive and repetitive training sessions (Borella et al, 2010;Carretti et al, 2012;Mozolic et al, 2011;Richmond et al, 2011;Smith et al, 2009) Maintenance was reported in nine out of ten cognitive training interventions, lasting between 3 and 6 months. These findings are consistent with reports from other reviews that training effects can be preserved for at least a couple of months in both memory and executive domains (Reijnders et al, 2012;Verhaeghen, 2000).…”
Section: Transfer and Maintenancesupporting
confidence: 67%
“…Contrary to prior reports (Owen et al, 2010;Papp et al, 2009) Papp et al, 2009;van Muijden et al, 2012;West, 2000), training most reliably produced transfer to tasks within the same cognitive domain, although seven cognitive training studies also reported transfer to untrained cognitive domains (Ball et al, 2002;Borella et al, 2010;Carretti et al, 2012;Cheng et al, 2012;Mozolic et al, 2011;Richmond et al, 2011;Smith et al, 2009). Consistent with research reporting that transfer depends on the type and duration of training (Klingberg, 2010;Owen et al, 2010;van Muijden et al, 2012), interventions using adaptive and repetitive training sessions (Borella et al, 2010;Carretti et al, 2012;Mozolic et al, 2011;Richmond et al, 2011;Smith et al, 2009) Maintenance was reported in nine out of ten cognitive training interventions, lasting between 3 and 6 months.…”
Section: Transfer and Maintenancementioning
confidence: 66%
See 2 more Smart Citations
“…In the current study, the Individual CT training context may have been more facilitative, simply due to the ostensible lack of distraction as compared to the busier and nosier Group CT setting. It has been suggested that distraction, and the decreased ability to focus without being distracted is one of the hallmarks, and conceivably one of the principal challenges to an elderly adult learner [33,34].…”
Section: Study Weaknesses and Future Directionsmentioning
confidence: 99%